82. Inter- and intraexaminer reliability of nerve conduction measurements in the upper limb of healthy subjects. Issue 12 (December 2017) - Diozzi, E.; Villani, G.; Bentivogli, S.; Di Bono, M.; Mussoni, P.; Simioni, V.; Sette, E.; Capone, J.G.; Tugnoli, V.
Abstract : To verify the test-retest, inter and intraexaminer variability of the Compound Muscle Action Potential (CMAP) and Sensory Nerve Action Potential (SNAP) within our neurophysiology laboratory; to identify the technical variables that can affect the reproducibility of signals in the follow-up studies. Distal CMAP of Median and Ulnar nerves and SNAP of radial nerve (I ° finger), median nerve (I° and IV° fingers), ulnar nerve (IV and V fingers) of the right hand were recorded by 9 operators (5 technicians of neurophysiology and 4 physicians) in healthy volunteers. Each test was repeated 3 times randomly within 4 months. The latency, amplitude, and intensity of stimulus were collected. The montages were photographed. Our data showed a discrete stability of CMAP parameters mainly for ulnar nerve. On the contrary the amplitudes of SNAPs were fairly variables. The results suggest that it is crucial to check the neurophysiological techniques commonly applied in laboratories were several operators work. More time must be dedicated to a common training, to get consistent results useful in repeated trials.